2010
DOI: 10.1056/nejmoa0907006
|View full text |Cite
|
Sign up to set email alerts
|

L-Histidine Decarboxylase and Tourette's Syndrome

Abstract: SummaryTourette's syndrome is a common developmental neuropsychiatric disorder characterized by chronic motor and vocal tics. Despite a strong genetic contribution, inheritance is complex, and risk alleles have proven difficult to identify. Here, we describe an analysis of linkage in a two-generation pedigree leading to the identification of a rare functional mutation in the HDC gene encoding Lhistidine decarboxylase, the rate-limiting enzyme in histamine biosynthesis. Our findings, together with previously pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
279
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(291 citation statements)
references
References 20 publications
9
279
0
3
Order By: Relevance
“…Interestingly, recent studies have indicated a role for histaminergic neurotransmission in the mechanism and modulation of Tourette's syndrome (Ercan-Sencicek et al, 2010) and the effect of L-dopa treatment in Parkinson's disease (Yanovsky et al, 2011), suggesting histaminergic drugs might well be efficacious for these and other disorders involving the basal ganglia (Schwartz, 2011). Last, the widespread projections of the histaminergic system suggest that histamine might modulate information processing similarly in widespread regions of the brain.…”
Section: Histamine Differentially Modulates Striatal Inhibitionmentioning
confidence: 99%
“…Interestingly, recent studies have indicated a role for histaminergic neurotransmission in the mechanism and modulation of Tourette's syndrome (Ercan-Sencicek et al, 2010) and the effect of L-dopa treatment in Parkinson's disease (Yanovsky et al, 2011), suggesting histaminergic drugs might well be efficacious for these and other disorders involving the basal ganglia (Schwartz, 2011). Last, the widespread projections of the histaminergic system suggest that histamine might modulate information processing similarly in widespread regions of the brain.…”
Section: Histamine Differentially Modulates Striatal Inhibitionmentioning
confidence: 99%
“…Much attention has been paid to dopaminergic candidates, and there is evidence of a significant association between TS and a dopamine transporter polymorphism (DAT1 Ddel) (Yoon et al, 2007b). Several recent candidate genes have included: a heterozygous loss of function mutation in L-histidine decarboxylase, which encodes the rate limiting enzyme in histamine biosynthesis (Ercan-Sencicek et al, 2010); functional variations of the SLITRK1 gene, with homology to a known axon guidance molecule (Scharf et al, 2008); and DLGAP3, a postsynaptic scaffolding protein highly expressed in striatal glutamatergic synapses (Crane et al, 2011).…”
Section: Etiologymentioning
confidence: 99%
“…Castellan Baldan et al 1, 2 report on characterization of a possible animal model for Tourette syndrome, chosen because of a family with Tourette syndrome linked to a loss-of-function mutation in the histidine decarboxylase gene 3, 4 . Histidine decarboxylase knock-out mice 5 exhibited tic-like stereotypies after a D-amphetamine challenge (see Figure 1, panel E in ref.…”
Section: Resultsmentioning
confidence: 99%